Salmonella isolated from raw chicken meats at selected slaughterhouses in Peninsular Malaysia; their antibiotic resistance profiles and biofilm formation on nutrient-limited media - Zuraidah Ismail,; Nur Naqiyah Azmi,; Nor Ainy Mahyudin,; Wan Hasyera Wan Omar,; Marina Abdul Rahman,; Marni Sapar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Salmonella is one of the pathogens responsible for foodborne diseases. Antibiotic resistance of Salmonella, particularly multidrug-resistant (MDR) strains have emerged and are becoming more prevalent, which is a very serious issue worldwide. This study sought to determine the antibiotic resistance profiles of Salmonella isolated from raw chicken meats, which were collected at selected slaughterhouses in Peninsular Malaysia and evaluating its biofilm-forming capability on surfaces. Antibiotic resistance of 135 Salmonella isolates against 12 antibiotics were investigated via disk diffusion method. The biofilm-forming ability of the isolates was evaluated by crystal violet staining using two media; a tryptic soy broth (TSB) and a 1/20 TSB with incubation periods of 24 and 48 h at 37 °C. A total of 118 strains of Salmonella showed higher resistance to erythromycin (87.41%), followed by tetracycline (85.19%;); 93 of the isolates (68.88%) were multi-drug resistant. A greater quantity of Salmonella was able to produce biofilm when grown in 1/20-TSB (90.37%) compared to the growth in TSB (88.15%), respectively. The findings in this study showed high prevalence, antibiotic resistance, and the biofilm forming ability of Salmonella strains isolated from raw chicken meats, suggesting that effective measures are required to ensure food safety in the poultry industry.